Testing Roman Glass in the Flame - Sue Heaser (EXARC Journal)
Glass made during the Romano British period was recycled throughout the Late Roman and Early Medieval periods. Studies have shown that British beadmakers of the fifth and early sixth centuries AD made a large proportion of their beads using Roman period glass (Peake, 2013). To study fully the techniques of glass workers in early Anglo-Saxon times, it is important to be sure the modern glass used to recreate ancient beads and other glass objects is similar in properties to the ancient glass used to make the originals. Glass with very different working properties could affect the techniques used. This study explains the importance of glass properties such as viscosity, temperature working range and softening point when studying ancient techniques of glass working. A quantity of Roman glass cullet, supplied by the Museum of London Archaeology, has been put to a range of tests, including beadmaking, to investigate the behaviour of the glass in the flame. The results show that the thermal expansion and viscosity of the ancient glass samples place them well within the range of modern artisan glasses used for beadmaking and glass fusing. The tests also revealed a wide variety of working properties in the samples, but the glass was all easily workable with more favourable properties than some modern glasses (See Figure 1).